Study on the effect and the mechanism of antimicrobial activity exerted by Syzygium aromaticum ethanolic extract - Wang, Yihe (fi=Turun yliopisto|en=University of Turku|, 2017)
Cloves (Syzygium aromaticum) are widely cultivated in Asian and African countries. Clove extract has therapeutic potential as an antimicrobial drug and food additives, since several studies have shown that it has strong antimicrobial activities and respond well to treatments of several diseases, such as toothache and wound inflammation. Nowadays, more and more antimicrobial drugs and food preservatives are developed from the nature. In order to find the molecular process of plant extract against microorganism, we chose clove bud which is the strongest plant among several natural plants based on preliminary tests. Main effective components and the stability of clove ethanolic extract were analyzed. Measurement of activity against several strains using the agar disk diffusion method and tube dilution method were performed. Effective volatile components in clove ethanolic extract were determined by Gas chromatography–mass spectrometry analysis. Storage stability and proper pH value of clove extract were analysed. Our results showed that clove extract displayed significantly antimicrobial effect to all the tested strains. Antifungal effect was stable within 6 months in the condition of -20°C and 4°C. Six main ingredients were identified, which accounted for 99.55% of the total extract. Using Saccharomyces cerevisiae (model), we observed there were no severe morphologically damaged on the cell wall, however, propidium iodide was stained DNA due to cell membrane permeability increased. Eukaryotic translation elongation factor 1 alpha (eEF1A) protein was found to be induced by clove ethanolic extract through sodium dodecyl sulphate-polyacrylamide gel electrophoresis assay. As a contrast, eugenol did not contribute much to this process. The mRNA level of eEF1A coding genes (TEF1, TEF2) was not affected significantly. However, mRNA level of other 7 genes (EFB1, ENO2, GSP1, RPP0, YEF3, TEF4, RPS2) which related to the function of eEF1A were highly increased. As a conclusion, the suppression of eEF1A protein by clove extract occurred only on protein translation stage and the suppression of eEF1A protein by clove extract did not significantly affect the transcription level of its coding genes (TEF1 and TEF2). Suppressing the expression of eEF1A could be a reason for cell growth inhibition. Our study analysed mechanism and possible cellular target of clove extract in S. cerevisiae and could provide scientific basis to the application of clove extract to many fields, such as natural antifungal drugs and food preservative.